Cultures of conflict: Protests, violent repression, and community values. (23rd April 2019) - Akkuş, Birol; Postmes, Tom; Stroebe, Katherine; Baray, Gamze
Abstract : What are the cultural origins of societal conflicts that revolve around democratization, women's rights, and modern libertarian values? We propose that deep‐seated differences in community‐based collective values (at the micro‐level) may be related to why people support anti‐government protest and why they support repression of such protests (at the macro‐level). The hypothesis was examined among residents of Turkey ( N = 500). Cultural values, measured at the individual level and community level with the community collectivism scale, correlated with political orientation and emotions, as well as with subsequent support for anti‐governmental protest or its repression. The main conclusions are that both support for protest and support for repression are related to the cultural values people hold and their subsequent political orientations and emotions. Micro‐level cultural values in local communities may thus play a role in explaining macro‐level socio‐political divides.